2006
DOI: 10.1016/j.chiabu.2005.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The impact of childhood sexual abuse in anorexia nervosa

Abstract: Objective: The aim of this study was to examine the impact of childhood sexual abuse (CSA) on clinical characteristics and premature termination of treatment in anorexia nervosa (AN). Method: The participants were 77 consecutive patients with AN admitted to an inpatient eating disorders unit. The patients were assessed in terms of eating disorder symptoms, general psychopathology, and CSA history at admission to hospital. Results: Thirty-seven patients (48%) reported a history of CSA before the onset of the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 50 publications
4
128
1
8
Order By: Relevance
“…51,52 Childhood sexual abuse may be more highly associated with symptoms of bulimia, such as binging and purging, because these behaviors can represent an attempt to regulate negative internal states, such as depression or anxiety, that can be the result of a history of childhood abuse. 51,53 Prior studies have suggested that values and norms in the gay male community place a heightened focus on physical appearance to which men may feel pressured to conform, thereby increasing the risk for eating disorders in this population. 5,54 While there might be validity to this explanation, our findings suggest that a history of childhood sexual abuse might also be an important factor in understanding what might place gay and bisexual men at risk for developing an eating disorder.…”
Section: Resultsmentioning
confidence: 99%
“…51,52 Childhood sexual abuse may be more highly associated with symptoms of bulimia, such as binging and purging, because these behaviors can represent an attempt to regulate negative internal states, such as depression or anxiety, that can be the result of a history of childhood abuse. 51,53 Prior studies have suggested that values and norms in the gay male community place a heightened focus on physical appearance to which men may feel pressured to conform, thereby increasing the risk for eating disorders in this population. 5,54 While there might be validity to this explanation, our findings suggest that a history of childhood sexual abuse might also be an important factor in understanding what might place gay and bisexual men at risk for developing an eating disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Posteriormente, outros trabalhos com achados negativos para tal associação deixaram menos claro qual o impacto do ASI para a anorexia nervosa 14 . Este estudo reforça, portanto, o papel do ASI como fator de risco, alinhando-se com a hipótese de que o ASI seria relevante também para a anorexia nervosa 15 , e não apenas para a bulimia nervosa, como vinha sendo descrito 13 .…”
Section: Discussionunclassified
“…Por outro lado, encontrou-se história de abuso sexual infantil antecedendo o início dos sintomas em aproximadamente 48% dos pacientes com anorexia nervosa. Além disso, mostrou-se também que a maior parte desses indivíduos encontrava-se no subtipo purgativo da doença, em vez do subtipo restritivo, denotando maior grau de psicopatologia no grupo mais afetado 15 . Uma explicação plausível é que comportamentos de purgação possam ajudar a modular estados internos negativos, que se assemelham aos efeitos emocionais do abuso 15 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Previous research investigating IPV among women with ED at other life points (not during the perinatal period) has been criticized for inadequately controlling for other factors that may influence the association between ED and IPV, particularly history of sexual abuse 11. Childhood sexual abuse has been associated with both ED19, 20, 21 and IPV in adulthood (revictimization) 22, 23. It is possible that the relationship between ED and IPV during and after the perinatal period may be partly due to the high levels of childhood sexual abuse among women with ED,11 or other factors associated with the pregnancy itself.…”
Section: Introductionmentioning
confidence: 99%